Red Ginseng Inhibits Scratching Behavior Associated With Atopic Dermatitis in Experimental Animal Models - Keiichi Samukawa; Yasukatsu Izumi; Masayuki Shiota; Takafumi Nakao; Mayuko Osada-Oka; Katsuyuki Miura; Hiroshi Iwao (Elsevier, 2012)
Pruritus is a severe symptom that is difficult to treat in atopic dermatitis patients. Red ginseng (RG), a natural medicine, has various biological activities such as anti-inflammatory effects. In this study, we examined the efficacy of RG extract (RGE) and its mechanism on experimental atopic dermatitis in mice. The effects of RGE on vascular permeability and itching were first evaluated. Histamine-induced permeability and itching were significantly inhibited by embrocation with RGE as well as diphenhydramine, an antihistamine drug. Next, we assessed the therapeutic effect of topical RGE in a mouse model of atopic dermatitis. Dermatitis was induced by repeated application of 2,4-dinitrofluorobenzene (DNFB) acetone solution to the mouse ear. The effects of tacrolimus (a calcineurin blocker), dexamethasone (a corticosteroid), and RGE on dermatitis and associated scratching behavior were compared. Repeated DNFB application caused frequent scratching behaviors and ear swelling. Topical treatment with tacrolimus, dexamethasone, and RGE for 8 days before the final challenge with DNFB significantly inhibited ear swelling. Tacrolimus and RGE significantly inhibited scratching behavior, whereas dexamethasone failed to do so. DNFB-induced nerve growth factor expression and nerve fiber extension were significantly attenuated by tacrolimus and RGE, but not by dexamethasone. RGE may have the potential for treatment of atopic dermatitis. Keywords:: atopic dermatitis, hapten, pruritus, red ginseng, substance P